Numerical analysis of the influence of leakage flows on flow and heat transfer processes under plastifying extrusion - Shcherbinin, Aleksey Grigorievich; Trufanova, Nataliya Mikhailovna; Ershov, Sergey Viktorovich (Computational Continuum Mechanics, 2014)
Heat and mass transfer processes in the channel of a plastifying extruder have been studied numerically with account for polymer melt leakage flows through the radial gap between the screw thread tip and the inner surface of the housing. This paper proposes an approach for identifying leakage flows through the gap just described by considering pressure and forced components of the polymer melt flow, abnormally viscous properties of the medium and uniform temperature fields in the channel cross-section. The approach can be used to develop mathematical (one-, two- or three-dimensional) models of fluid flows in the channels of simple screw pumps and plastifying extruders for dosing and melting zones. The equations of motion and the incompressibility equation are solved in natural variables by the Galerkin method using finite elements. A solution to the energy equation is found by the finite difference method with convective terms written in a counter-flow direction. A multilevel iterative algorithm is developed for the problem of heat and mass transfer processes in the screw channel of the extruder with considerations of polymer melt leakage flows through the radial gap. Velocity, temperature and pressure fields in the extruder screw channel and in the gap above the screw are obtained from the numerical experiments. The influence of the leakage flow through the radial gap on the temperature fields of the screw channel and the output performance and the pressure drop-flow rate characteristics of a plastifying extruder is determined.
Keywords: finite element method; finite difference method; heat and mass transfer; polymer melt flow; plastifying extrusion; leakage flows